Changing teachers' beliefs regarding autonomy support and structure: The role of experienced psychological need satisfaction in teacher training. (March 2016) - Aelterman, Nathalie; Vansteenkiste, Maarten; Van Keer, Hilde; Haerens, Leen
Abstract: Objectives: Grounded in Self-Determination Theory, this study examined whether physical education (PE) teachers' psychological need satisfaction experienced during continuous professional development (CPD) on need-supportive teaching predicted changes in their effectiveness and feasibility beliefs regarding the proposed teaching approach, as well as their intentions to apply this approach and subsequent changes in their self-reported in-class behaviors. Methods: Prior to the training, a sample of 80 PE teachers (57.5% men, M age = 42.70 ± 10.15 years) reported on their effectiveness and feasibility beliefs regarding autonomy-supportive and structuring teaching strategies and their in-class application of these strategies. Immediately following the training, these beliefs were assessed again and participants reported on their psychological need satisfaction experienced during the training and their intentions to apply the proposed strategies. Finally, two weeks after the training, participants' self-reported in-class application of the teaching strategies was measured for the second time. Results: Psychological need satisfaction experienced during the training related to a change in effectiveness and feasibility beliefs regarding autonomy support and structure, and to teachers' intentions to apply the proposed strategies as reported immediately after receiving the training. In addition, teachers' intentions related to a change in their self-reported in-class application of structuring, but not autonomy-supportive, teaching strategies. Conclusions: Experiences of psychological need satisfaction during CPD can help to increase the likelihood that teachers become more convinced about the effectiveness and feasibility of the proposed change and can produce greater intentions toward change, which may relate to actual (albeit) self-reported behavior change. Highlights: We examine how experienced need satisfaction during CPD relates to teacher change. Experienced need satisfaction increases perceived effectiveness and feasibility. Need satisfaction directly fosters teachers' intentions to apply proposed change. In turn, intentions relate to changes in self-reported in-class teaching behavior. It is critical to maximize opportunities for need satisfaction during CPD.